Peran Minyak Kayu Putih Terhadap Karakteristik Pembakaran Minyak Kapuk Sebagai Bahan Bakar Alternatif - Riupassa, Helen (Fakultas Teknik UMSU, 2023)
The study conducted experimental investigations on the burning rate of crude kapuk oil droplets by incorporating bio-additives derived from eucalyptus oil. The bio-additive concentration of eucalyptus oil added to the kapuk oil was 100 ppm and 300 ppm, respectively. The droplet combustion method was chosen to maximize the contact area between the air and fuel, thereby enhancing the reactivity of fuel molecules.The findings revealed that the cineol compounds present in eucalyptus oil exhibit aromatic properties and possess an asymmetrical carbon chain geometry. This characteristic has the potential to facilitate effective collisions among fuel molecules, thereby promoting combustion. This was evident from the observed increase in the burning rate. Furthermore, the observations indicated that the highest burning rate was achieved when both bio-additives were 300 ppm.These results highlight the positive impact of incorporating eucalyptus oil as a bio-additive in crude kapuk oil. The aromatic nature and unique geometric structure of cineol compounds contribute to the fuel's increased reactivity and enhanced combustion performance. By utilizing bio-additives, such as eucalyptus oil, at an optimal concentration, it is possible to further improve kapuk oil's burning characteristics and overall performance as a biofuel.These findings provide valuable insights into the development of more efficient and sustainable alternative energy sources. By understanding the molecular aspects and effects of bio-additives, researchers can continue to explore and optimize the utilization of biofuels, such as crude kapuk oil, for a greener and more environmentally friendly energy future.